Market Potential and Distance Decay - Growth and decline of sectors across locations in urban regions - Johan Klaesson; Börje Johansson (European Regional Science Association (ERSA), 2013)
This paper introduces a model which identifies the economic activity of each local economy (location) and observes the time distance between each pair of locations as well as the average time distance between sub locations in each local economy. We focus on three categories of firms: (i) manufacturing, (ii) KIBS, and (iii) other services and model how they increase and decrease their employment in each location in response to the location?s market potential. The response mechanism allows for non-linearities and aims to show how the dynamic response differs for the three categories of firms. In the econometric analysis the market potential of each location is determined endogenously, and this also makes it possible to determine the geographic extension of urban regions. This exercise also includes an endogenous determination of sector-specific distance-decay parameters. The model succeeds in depicting the gradual increase of service activities in certain locations and manufacturing activities in others.
Keywords: 330; Market Potential; Distance Decay; Employment growth; Non-linear